SEROLOGICAL EVIDENCE OF THE PRESENCE OF CANINE HERPES VIRUS TYPE 1 IN LIMA PROVINCE - Góngora A., Vladimir (2007)
The canine Herpesvirus type 1 (CHV-1) is responsible for the canine hemorrhagic disease in puppies aged less than four weeks and for some reproductive problems in adult bitches. In Peru, the disease has been not reported, although there are findings suggesting its presence. Thus, the aim of this study was to show the presence of antibodies against CHV-1 among the canine population associated with history of reproductive problems. Blood samples from 28 animals belonging to seven districts of the province of Lima were collected. These dogs had a history of reproductive problems or neonatal mortality. Samples were submited to the indirect immunofluorescense test (IFAT), and nine of them (32 ± 17%) were positive to the test.